2021
DOI: 10.1080/20477724.2021.1927605
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between COVID-19 Severity and Bacillus Calmette-Guérin (BCG)/ Mycobacterium tuberculosis exposure history in healthcare workers: a multi-center study

Abstract: The COVID-19 pandemic has brought countries’ health services into sharp focus. It was drawn to our group’s attention that healthcare workers (HCWs) had a lower mortality rate against higher COVID-19 incidence compared to the general population in Turkey. Since risk of exposure to tuberculosis bacillus among healthcare workers are higher than the population, we aimed to investigate if there is a relationship between BCG and Mycobacterium tuberculosis exposure history with COVID-19 severit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In a study investigating the effect of TB contact and BCG vaccination on the course of COVID‐19 in healthcare workers, it was found that the rate of BCG vaccination was higher in those with a history of COVID‐19‐related hospitalization, in contrast to many studies in the literature and our results. In the same study, higher mean TST results were found in outpatients compared to inpatients, although there was no significant difference 30 . We observed that patients with positive TST results were significantly more likely to have mild COVID‐19 disease compared to those with negative TST, too.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…In a study investigating the effect of TB contact and BCG vaccination on the course of COVID‐19 in healthcare workers, it was found that the rate of BCG vaccination was higher in those with a history of COVID‐19‐related hospitalization, in contrast to many studies in the literature and our results. In the same study, higher mean TST results were found in outpatients compared to inpatients, although there was no significant difference 30 . We observed that patients with positive TST results were significantly more likely to have mild COVID‐19 disease compared to those with negative TST, too.…”
Section: Discussionmentioning
confidence: 42%
“…In the same study, higher mean TST results were found in outpatients compared to inpatients, although there was no significant difference. 30 We observed that patients with positive TST results were significantly more likely to have mild COVID-19 disease compared to those with negative TST, too.…”
Section: Discussionmentioning
confidence: 53%
“…Other study basing on surveys (n = 1,233) suggested that intake of BCG in childhood may increase risk of COVID-19 infection [33]. A Turkish multi-centre study suggests that exposition to M. tuberculosis (infected patient or vaccine) results with more severe course, but lower mortality to COVID-19 in healthcare workers [34]. An Italian survey-based research showed no significant difference in COVID-19 prevalence among physicians vaccinated by BCG [35].…”
Section: Clinical Datamentioning
confidence: 99%
“…These fall into two categories ( 1 ): the effect of childhood BCG vaccination on COVID-19 and ( 2 ) the effect of re-vaccination on COVID-19 in adults. BCG vaccination in childhood was associated with decreased SARS-CoV-2 prevalence or mortality among health care workers ( 44 , 45 ); however, in clinical studies, the protective effect of re-vaccination with BCG in adults was controversial. One randomized clinical trial showed that BCG vaccination in the elderly was correlated with lower incidence of SARS-CoV-2 infection ( 46 ).…”
Section: Use Of Lavs For Control Of Newly Emerging Virusesmentioning
confidence: 99%